PENGARUH SISTEM INFORMASI DAN KINERJA LOGISTIK TERHADAP KEPUASAN PELANGGAN : Studi Kasus Pada Pelanggan J&T - Deryl Kresna, Nirwaseta; Mohammad, Mukhsin (STIE PGRI Dewantara Jombang, 2023)
This research investigates the relationship between information systems, logistics performance, and customer satisfaction. The object of this research study is the J&T logistics company, which has an extensive network in Indonesia and uses the latest information system as a web-based application. The population of this study was J&T logistics service customers in Cilegon, and the sample was 95 people. The data used is primary data processed using the SPSS application. The research results show that the information system does not affect customer satisfaction. However, J&T's logistics performance has a significant effect on customer satisfaction.